The trimoni twins and the shrunken treasure - Smallcomb, Pam. (London : Bloomsbury, 2005)
Two magical twin sisters help a modelmaker and a handsome young movie star find a lost treasure in Amsterdam.
Keywords: Fiction -- 9-12.; Magic -- Fiction; Sister -- Fiction; Twins -- Fiction